2019
DOI: 10.4274/tjo.galenos.2018.67670
|View full text |Cite
|
Sign up to set email alerts
|

Purtscher-Like Retinopathy Associated with Synthetic Cannabinoid (Bonzai) Use

Abstract: Purtscher’s retinopathy is a microvascular occlusive disease initially described as retinal edema, cotton wool-like exudation, and hemorrhages occurring after severe head trauma. A similar clinical presentation called Purtscher-like retinopathy is associated with systemic diseases instead of trauma. In the present case, ophthalmic eksamination of a patient with complaints of blurred vision related to substance (Bonzai) use revealed bilateral cotton-wool spots. Purtscher-like retinopathy was diagnosed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…OCT mostly indicates retinal oedema at the macula. Recent studies have reported cystoid macular oedema or even subretinal fluid in patients with PUR [7]. PAMM lesions, a special OCT feature of PUR discovered in recent years, present as hyperreflective bands at the INL in OCT, indicating an ischaemic condition at the outer retinal capillary plexus [8].…”
Section: Discussionmentioning
confidence: 99%
“…OCT mostly indicates retinal oedema at the macula. Recent studies have reported cystoid macular oedema or even subretinal fluid in patients with PUR [7]. PAMM lesions, a special OCT feature of PUR discovered in recent years, present as hyperreflective bands at the INL in OCT, indicating an ischaemic condition at the outer retinal capillary plexus [8].…”
Section: Discussionmentioning
confidence: 99%
“…OCT mostly indicates retinal oedema at the macula. Recent studies have reported cystoid macular oedema or even subretinal fluid in patients with PUR[7]. PAMM lesions, a special OCT feature of PUR discovered in recent years, present as hyperreflective bands at the INL in OCT, indicating an ischaemic condition at the outer retinal capillary plexus[8].This patient also presented low perfusion in the retina layer.…”
mentioning
confidence: 84%